Analisis Nilai Karakter dalam Lagu Anak Tradisional Banjar “Kakanakan Sungai Martapura” - Riski Sugiteriyana; Haswinda Harpriyanti (Continuous Education: Journal of Science and Research, 2026)
Traditional children's songs are part of oral literature that function not only as entertainment but also as a medium for transmitting cultural values, moral teachings, and community identity. The rapid development of digital technology has influenced children's familiarity with local traditional songs, causing many regional songs to experience a decline in use among younger generations. Therefore, scientific studies are needed to reveal the educational values contained in traditional children's songs. This study aims to analyze the character values embedded in the traditional Banjar children's song entitled “Kakanakan Sungai Martapura.” This research employed a qualitative approach with a descriptive method. The research data consisted of the lyrics of the song “Kakanakan Sungai Martapura” as primary data and relevant literature on oral literature, character education, and Banjar culture as secondary data. Data were collected through documentation, lyric transcription, translation, and identification of character values contained in the lyrics. Data analysis was conducted using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The results revealed four main character values found in the song, namely friendliness or communicativeness, hard work, independence, and love for the homeland. These values are reflected through children's activities in interacting, playing, facing challenges in the river environment, and expressing attachment to local cultural identity. This study demonstrates that Banjar traditional children's songs contribute as a culturally based medium for character education. The utilization of traditional songs in learning activities can serve as an alternative strategy to strengthen children's moral development while preserving Banjar cultural heritage.